Reconstruction of Small and Medium-Sized Nasal Defects Using an Omega Advancement Flap. Issue 3 (May 2020) - Altun, Serdar; Bal, Ali; Arpaci, Enver
Abstract : Introduction: The nose is the most common area where malignant skin tumors occur. Repair with a flap after tumor excision provides esthetically and functionally acceptable results. In this study, we aimed to present the use of an omega (Ω) advancement flap, which can be applied in all anatomic regions of the nose, in 2 cm or smaller defects. Methods: Between 2015 and 2017, 18 patients underwent repair with omega (Ω) advancement flap in the nose after tumor removal. The pathology of 17 patients was basal cell carcinoma, and keratoacanthoma in 1 patient. The average defect diameter was 1.6 × 1.56 cm. The defects were in the nasal tip, nasal wing, lateral nasal wall, and supratip region. After tumors were excised from the safe margin, and were repaired using an omega advancement flap in the same session. Results: No flap necrosis, dehiscence, or infection was observed in the early postoperative period. Three patients developed hematoma under the flap, which was drained. No tumor recurrence was observed during the postoperative follow-up period. The results were satisfactory in all patients. Conclusion: The omega advancement flap is a safe procedure that can be easily applied in the same session for the repair of small-to-medium-sized nasal defects. Abstract : Supplemental Digital Content is available in the text